Jamaica's Food Stamp Program : Impacts on Poverty and Welfare - Ezemenari, Kenechukwu Maria 1997- (The World Bank, 1999)
Without the food stamp program, the poverty gap in Jamaica would have been much worse during the early 1990s, when the Jamaican dollar was being devalued. Households with elderly members and young children benefited most from the program. - Ezemenari and Subbarao examine how the food stamp program affected measures of poverty during devaluation of the Jamaican dollar in the early 1990s. They find that without the food stamp program, the poverty gap in Jamaica would have been much worse, especially in 1990 and 1991. For the country as a whole, not having a food stamp program wouldn't have affected the incidence of poverty significantly, but particular groups among the poor would have fared worse. Households with elderly residents benefited most from the program. Households with young children benefited more than households without, in terms of the poverty headcount and gap. The program also appears to have had more effect on extremely poor households than on those of the transient poor (people who move in and out of poverty). Explicitly incorporating behavioral responses into the model reduces the contribution of food stamps to household consumption and poverty, but the poorest benefited most from the program even after accounting for behavioral responses. The program contributed more to reducing poverty than to smoothing consumption. This paper - a product of the Poverty Division, Poverty Reduction and Economic Management Network - was presented at the World Bank Institute workshop Evaluating the Impact of Development Interventions: Concepts, Methods and Cases, December 9-10, 1998. The authors may be contacted at kezemenari@worldbank.org or ksubbarao@worldbank.org